Agarwood Production of Aquilaria malaccensis Using Various Inoculants and Induction Techniques - Mustapa, Mohd Zamakhsyary; Alias, Mohd Azani; Azziz, Saripah Salbiah Syed Abdul; Wong, Chee Fah; Ibrahim, Mastura; Yahaya, Rozita; Bakri, Yuhanis Mhd; Rajak, Noorazrin Abdul (CENTRAL ASIA AND THE CAUCASUS, 2022)
Agarwood, the fragrant resinous wood of Aquilaria species, is precious and widely used in medicine, religion, and perfume. Aquilaria malaccensis cultivation and inoculation techniques have been successfully developed in Malaysian plantations to protect endangered Aquilaria species. Several inoculation techniques have been explored in local plantations to stimulate the agarwood resin in a short period. Therefore, in this paper, five inoculants and four methods of inductions were analysed and compared for their effectiveness. Two phases of agarwood harvesting were executed after 18 months and 24 months of the incubation period. The results showed that inoculant IGB711 had effectively stimulated the agarwood formation during 24 months of incubation with mean yield 25.76 kg/tree. Meanwhile, the RAHE Probio inoculant, in combination with the bamboo stick and dripping method, was effective in producing high-quality agarwood. With the latest induction technologies developed in Malaysia plantations, it is now possible to cultivate high-value agarwood in young plantation trees.